Precaução e direcionamento de condutas sob incerteza científica - Fraga, Júlia Massadas Romeiro (2019)
This dissertation aims to analyze the meaning, structure and forms of application of the so-called precautionary principle (PP) as a regulatory tool for directing conduct under conditions of scientific uncertainty based on a bibliographical review and empirical study of the jurisprudence of the Brazilian Supreme Court (STF) on the theme. PP is often invoked as an important instrument for protecting the environment and human health against economic activities with the potential to cause serious and irreversible damages, in that it prevents the lack of scientific evidence regarding the effects of a given activity to justify the inertia in the adoption of precautionary measures to avoid the risks of damages that it may cause. However, despite being considered by many as a fundamental principle of environmental law and having gained a prominent position on the international scene, its meaning and form of application are generally neglected. That is, while PP is widely advocated as crucial in environmental management, its normative definition is still imprecise and little is said about its form of application. It should be noted that the definitions thereof are vague, widely varying, and give little (or no) direction to their applicator. In view of this, the objective of this dissertation is to analyze the multiple meanings of the PP, the context in which it is inserted and the justifications for its adoption, distinguishing also its different versions and explaining if it would indeed have an essential and exclusively prohibitive nature ("zero risk"). Starting from the research problem of whether the PP would be a regulatory instrument capable of directing conducts under conditions of scientific uncertainty, the purpose is to scrutinize the parameters that it confers for the regulatory policy, as well as how the STF interprets and applies it, evaluating the criteria adopted by the court. And, considering that its implementation involves a series of controversies, this work aims to present the questions about the adoption of excessively conservative measures and of risk aversion, which could inhibit economic development and scientific progress. It will be therefore explored the criticisms commonly addressed to the PP, the existing answers and normative interpretations that aim to guarantee a moderate application of it, as well as reflections on the role that it plays in the current Brazilian context. It is concluded that, in order to be effectively implemented, the PP must present clear criteria for its application in order to differentiate types of risks whose degree and damage justify or not the adoption of precautionary measures. Otherwise, its misapplication can lead to abuses and selectivity, giving excessive discretion to decision makers, generating additional costs, distorting regulatory priorities, favoring irrational fears, and inhibiting innovation and development through prohibitive practices. If maintained a vagueness about its concept and form of application, this can corroborate the exercise of a purely rhetorical function by the PP, without it having a practical effectiveness, which would lead to a negative emptiness of its importance.